RNA Drugs - Linh, Nguyen Hue; Hue, Pham Thi Minh; Binh, Nguyen Thi Thanh; Thanh Tung, Bui; Loi, Vu Duc; Yen, Nguyen Thi Hai; Hai, Nguyen Thanh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 1, 2022)
RNA drugs are a new group of drugs that delivers RNAs or similar structures inside the body to achieve the therapeutic effect. This is a promising direction in drug development to treat serious and rare genetic diseases more specifically and effectively. In reality, the genetic systems and protein synthesis processes of living organisms are extremely complex, so the development of RNA drugs faces many difficulties. To achieve success, many different studies have been carried out to address issues such as finding suitable RNAs, synthesizing similar RNA structures, stabilizing RNA structures, and introducing drugs into targeted cells. Since the first RNA drug was officially approved by the FDA (2004), 10 RNA drugs in total have been approved to date. Among them, two vaccines, appearing at the time when much needed support to cope with the new SARS-CoV-2 variants, were developed using mRNA technology. With these achievements, scientists can have more confidence in the possibilities of evolving a new drug group that is more specific and effective, which is RNA drugs. This review briefly introduces the group of drugs that use RNAs, RNA structural analogs, and RNA biomarkers to develop novel drugs for application in the diagnosis, prevention, and treatment of disease. Keywords: RNA drugs; mRNA; the protein; vaccines; RNA diagnostics; small molecule drugs; RNA target. References [1] U. Sahin, K. Karikó, Ö. Türeci, Mrna-Based Therapeutics-Developing A New Class of Drugs, Nature Reviews Drug Discovery, Vol. 13, No. 10, 2014, pp. 759-780. [2] T. H. Nguyen, T. M. H. Pham, M. K. Tu, Pharmacogenetics: Prospects and Issues. Journal of Pharmacy, No. 54, Vol. 456, 2014, pp. 2-6. [3] A. M. Yu, Y. H. Choi, M. J. Tu, Rna Drugs and Rna Targets for Small Molecules: Principles, Progress, and Challenges, Pharmacological Reviews, Vol. 72, No. 4, 2020, pp. 862-898. [4] M. A. Hendaus, F. A. Jomha, Mrna Vaccines for Covid-19: A Simple Explanation, Qatar Medical Journal, Vol. 2021, No. 1, 2021, pp. 1-5. [5] A. Banerji, P. G. Wickner, R. Saff, C. A. Stone Jr, L. B. Robinson, A. A. Long et al., Mrna Vaccines to Prevent Covid-19 Disease and Reported Allergic Reactions: Current Evidence and Suggested Approach, the Journal of Allergy and Clinical Immunology: in Practice, Vol. 9, No. 4, 2021, pp. 1423-1437. [6] https://www.Fda.Gov/Emergency-Preparedness-and-Response/Coronavirus-Disease-2019-Covid-19/Covid-19-Vaccines (accessed on: December 15th, 2021). [7] E. H. Aarntzen, G. Schreibelt, K. Bol, W. J. Lesterhuis, A. J. Croockewit, J .H. De Wilt et al., Vaccination with Mrna-Electroporated Dendritic Cells Induces Robust Tumor Antigen-Specific Cd4+ and Cd8+ T Cells Responses in Stage Iii and Iv Melanoma Patients, Clinical Cancer Research, Vol. 18, No. 19, 2012, pp. 5460-5470. [8] H. M. Phan, K. L. Vu, T. H. Nguyen, T. T. Bui, A Comprehensive Review of Vaccines Against Covid-19, VNU Journal of Science: Medical and Pharmaceutical Sciences, Vol. 37, No. 3, 2021, pp. 1-19 (in Vietnamese). [9] N. Pardi, M. J. Hogan, F. W. Porter, D. Weissman, Mrna Vaccines - A New Era in Vaccinology, Nature Reviews Drug Discovery, Vol. 17, No. 4, 2018, pp. 261-279. [10] G. Wen, T. Zhou, W. Gu, The Potential of Using Blood Circular Rna As Liquid Biopsy Biomarker for Human Diseases. Protein & Cell, Vol. 12, No. 12, 2021, pp. 911-946. [11] S. Sabarimurugan, C. Kumarasamy, S. Baxi, A. Devi, R. Jayaraj, Systematic Review and Meta-Analysis of Prognostic Microrna Biomarkers for Survival Outcome in Nasopharyngeal Carcinoma. Plos One, Vol. 14, No. 2, 2019, pp. 1-18. [12] F. Wang, T. Zuroske, J. K. Watts, Rna Therapeutics on the Rise, Nat Rev Drug Discov, Vol. 19, No. 7, 2020, pp. 441-442. [13] E. J. Wild, S. J. Tabrizi, Therapies Targeting Dna and Rna in Huntington's Disease, The Lancet Neurology, Vol. 16, No. 10, 2017, pp. 837-847. [14] H. Han, Rna Interference to Knock Down Gene Expression, Disease Gene Identification, 2018, pp. 293-302. [15] J. Kim, C. Hu, C. M. E. Achkar, L.E. Black, J. Douville, A. Larson et al., Patient-Customized Oligonucleotide Therapy for A Rare Genetic Disease, New England Journal of Medicine, Vol. 381, No. 17, 2019, pp. 1644-1652. [16] U. Food, D. Administration, Fda Approves First-of-Its Kind Targeted Rna-Based Therapy to Treat A Rare Disease, Silver Spring (Md): Usfda, 2018. [17] E. Sardh, P. Harper, M. Balwani, P. Stein, D. Rees, D. M. Bissel et al., Phase 1 Trial of An Rna Interference Therapy for Acute Intermittent Porphyria, New England Journal of Medicine, Vol. 380, No. 6, 2019, pp. 549-558. [18] G. Devi, Sirna-Based Approaches in Cancer Therapy, Cancer Gene Therapy, Vol. 13, No. 9, 2006, pp. 819-829. [19] T. G. Hopkins, M. Mura, H. A. A. Ashtal, R. M. Lahr, N. A. Latip, K. Sweeney et al., The Rna-Binding Protein Larp1 Is A Post-Transcriptional Regulator of Survival and Tumorigenesis in Ovarian Cancer, Nucleic Acids Research, Vol. 44, No. 3, 2016, pp. 1227-1246. [20] V. Iadevaia, M. D. Wouters, A. Kanitz, A. M. M. González, E. E. Laing, A. P. Gerber, Tandem Rna Isolation Reveals Functional Rearrangement of Rna-Binding Proteins on Cdkn1b/P27 Kip1 3’utrs in Cisplatin Treated Cells, Rna Biology, Vol. 17, No. 1, 2020, pp. 33-46. [21] T. T. Bui, K. S. Phan, T. M. H. Pham, T. H. Nguyen, PEGylation of Curcumin and Prospect of Application, VNU Journal of Science: Medical and Pharmaceutical Sciences, Vol. 32, No. 1, 2016, pp 1-11.